2019
DOI: 10.1186/s12941-019-0335-8
|View full text |Cite
|
Sign up to set email alerts
|

A 7-year surveillance of the drug resistance in Klebsiella pneumoniae from a primary health care center

Abstract: BackgroundThe increased prevalence of Klebsiella pneumoniae infections and resistance rates are a current cause for concern. However, data for resistance rates in K. pneumoniae strains from primary hospitals and the resistance distribution among the different isolate sample sources are scarce.MethodsAll the K. pneumoniae strains were isolated from patients who visited a primary health care center located in Central Zhejiang Province from January 2011 to December 2017. The specimens included blood, sputum, cerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…Among the different specimen types examined in this study, our results showed that K. pneumoniae isolates from urine were much more likely to be carbapenem-resistant than those isolated from sputum or blood. Although studies examining risk factors associated with CRKP carriage are limited, one study of ESBL-producing K. pneumoniae demonstrated that the isolation rate of ESBL-positive isolates from urine samples was significantly higher than those from blood and sputum [17].…”
Section: Discussionmentioning
confidence: 99%
“…Among the different specimen types examined in this study, our results showed that K. pneumoniae isolates from urine were much more likely to be carbapenem-resistant than those isolated from sputum or blood. Although studies examining risk factors associated with CRKP carriage are limited, one study of ESBL-producing K. pneumoniae demonstrated that the isolation rate of ESBL-positive isolates from urine samples was significantly higher than those from blood and sputum [17].…”
Section: Discussionmentioning
confidence: 99%
“…19 The incidence of urinary tract infections caused by ESBL-KP has steadily increased in the US, and it has been shown that KP isolates from blood and urine are more carbapenem-resistant than sputum culture isolates. 17,20 In this study, CRKP patients were mainly concentrated in the population aged ≥70 years (80.9%) and neonates <1 year (16.2%). In addition, age over 70 years old was shown as a risk factor for CRKP and ESBL-KP infection.…”
Section: Discussionmentioning
confidence: 70%
“…However, the finding was comparable to a study in the tertiary hospital in Korea by Kang et al [52], where a CRE carriage rate on admission in 833 adults was 2.8%. Similarly, less than 2% CRKP was recorded in 7-year surveillance study in a primary health care centre in China [53]. However, in Brazil, a 6.8% CRE colonization rate has been reported on admission [54].…”
Section: Discussionmentioning
confidence: 96%